Analysis and selection of harmonics sensitive to demagnetisation faults intended for condition monitoring of double rotor axial flux permanent magnet synchronous machines. Issue 4 (15th February 2018) - De Bisschop, Jan; Abdallh, Ahmed Abou‐Elyazied; Sergeant, Peter; Dupré, Luc
Abstract : Yokeless and segmented armature (YASA) axial flux permanent magnet synchronous machines may have asymmetrical demagnetisation defects in their two rotors. Condition monitoring, therefore, becomes more complicated than in conventional single rotor machines. To develop a real‐time condition monitoring algorithm for demagnetisation faults in YASA machines – which requires solving an inverse problem – a fast forward model is necessary. A frequency‐based analytical model is used to calculate the three‐phase terminal voltages based on the three‐phase current waveforms and the demagnetisation defects including asymmetrical defects in the two rotors. To reduce the computational time of the forward model, this study focuses on the sensitivity of different voltage harmonics on several demagnetisation faults. To this end, the Cramér–Rao lower bound technique is used to analyse the harmonics sensitivity to the demagnetisation faults. The goal of the sensitivity analysis is to select an appropriate set of harmonics that gives maximal information about the defects. It becomes much faster and useful for real‐time condition monitoring. The results of the analysis show that the subharmonics around and including the fundamental are the most sensitive harmonics to the demagnetisation defects. The analytical model is validated with experimental data and finite element simulations.